Individualization: The function of unconscious - Jungas, Karlas Gustavas (Psichologija, 1997)
The article presents an excerpt from one of the most known essay of Jung in which he analyzes the functions of unconscious, its structure and dynamics, and the relation of conscious and unconscious.